2023
DOI: 10.1101/2023.03.28.534295
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cultured Mesenchymal Cells from Nasal Turbinate as a Cellular Model of the Neurodevelopmental Component of Schizophrenia Etiology

Abstract: Study of the neurodevelopmental molecular mechanisms of schizophrenia requires the development of adequate biological models such as patient-derived cells and their derivatives. We previously used cell lines with neural progenitor properties (CNON) derived from superior or middle turbinates of patients with schizophrenia and control groups to study gene expression specific to schizophrenia. In this study, we compared single cell-RNA seq data from two CNON cell lines, one derived from an individual with schizop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
(76 reference statements)
1
3
0
Order By: Relevance
“…This team presented their new study in this special topic, describing a protocol for an efficient manufacturing process for clinical-grade olfactory stem cells, which could be used to promote the recovery of spinal cord trauma, hearing loss, Parkinson's disease, amnesia, and peripheral nerve injury (Jaloux et al). Mesenchymal cells derived from the respiratory epithelium of the middle or superior turbinates are very similar to the cells in the embryonic brain (Tung et al, 2023), further supporting the idea of the important role of mesenchymal cells in brain disorders.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…This team presented their new study in this special topic, describing a protocol for an efficient manufacturing process for clinical-grade olfactory stem cells, which could be used to promote the recovery of spinal cord trauma, hearing loss, Parkinson's disease, amnesia, and peripheral nerve injury (Jaloux et al). Mesenchymal cells derived from the respiratory epithelium of the middle or superior turbinates are very similar to the cells in the embryonic brain (Tung et al, 2023), further supporting the idea of the important role of mesenchymal cells in brain disorders.…”
supporting
confidence: 54%
“…Studies of the ON as a model system of brain development and neurodegeneration have shown impressive evolution, accommodating new technologies, such as epigenetic methodologies (Rhie et al, 2018) and single-cell transcriptomics (Oliva et al, 2022;Tung et al, 2023), and they are growing in scale (Evgrafov et al, 2020). This topic demonstrates increased diversity and new dimensionalities, widening the borders of cell models to use them for drug discovery (Mihaljevic et al) and for cell therapy (Jaloux et al) as well as continuing the addition of conditions that could be modeled by cells from the ON (Fang et al).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously we used superior turbinate and middle turbinate biopsies to produce cell lines with neural progenitor characteristics (CNON), 53 and we identified in this study mesenchymal cells as a cell type with an expression profile very close to CNON (expressing ACTA2, MAP1B , and COL1A2) thus being likely a precursor of CNON ( Figure 5 ). 54 Endothelial cells were characterized by expression of ACKR1 , SELE , SOX18, MME , EDN1 , PLVAP , and VWF ( Figure 6 ). 55 …”
Section: Resultsmentioning
confidence: 99%